2010
DOI: 10.1007/s00203-010-0595-3
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase isozymes from a psychrotrophic bacterium, Pseudomonas psychrophila

Abstract: The genes encoding monomer-and dimer-type isocitrate dehydrogenase (IDH) isozymes from a psychrotrophic bacterium, Pseudomonas psychrophila, were cloned and sequenced. Open reading frames of the genes were 2,226 and 1,257 bp in length and corresponded to polypeptides composed of 741 and 418 amino acids, respectively. The deduced amino acid sequences showed high sequence identity with those of psychrophilic bacteria, Colwellia maris and Colwellia psychrerythraea, (about 70% identity) and the respective types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Various psychrophilic enzymes [178, 184, 248250, 275282] have been engineered in order to check the involvement of specific adaptive mutations within or close to the active site. These studies have revealed a complex pattern of effects on kinetic parameters, activation energy, and stability that cannot be interpreted in simple terms.…”
Section: Activity-flexibility-stability Relationships: Current Issuesmentioning
confidence: 99%
“…Various psychrophilic enzymes [178, 184, 248250, 275282] have been engineered in order to check the involvement of specific adaptive mutations within or close to the active site. These studies have revealed a complex pattern of effects on kinetic parameters, activation energy, and stability that cannot be interpreted in simple terms.…”
Section: Activity-flexibility-stability Relationships: Current Issuesmentioning
confidence: 99%
“…Many bacteria, including Escherichia coli, possess only one of either type IDH [1,2,5,6,17]. However, psychrophilic bacteria, Colwellia maris strain ABE-1 (JCM 10085) [20,26] and Colwellia psychrerythraea [3,4], and a psychrotolerant bacterium, Pseudomonas psychrophila strain E-3 (JCM 10889) [19,27], have been found to hold both of the two type IDHs [13][14][15][16]. Although these two types of IDH catalyze the same reaction, their amino acid sequences and immunological cross-reactivities are different from each other [6][7][8]17].…”
Section: Introductionmentioning
confidence: 99%
“…tuberculosis , P . psychrophila or Vibrio sp ., have two structurally different isozymes [1,57]. For example, both C .…”
Section: Introductionmentioning
confidence: 99%